2019
DOI: 10.3390/su12010239
|View full text |Cite
|
Sign up to set email alerts
|

Why Employees Contribute to Pro-Environmental Behaviour: The Role of Pluralistic Ignorance in Chinese Society

Abstract: In light of the importance of sustainable development, this study aims to deepen and extend our understanding of employees’ pro-environmental behaviour in the workplace in a Chinese context. Drawing on the complex phenomenon of social norms theory concerning misperceptions (i.e., pluralistic ignorance) and supervisor–subordinate guanxi (which is a Chinese term signifying human connection), we present a novel model in which employees’ pro-environmental behaviour is the result of multiple social and individual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…Employees' PEB is a series of environmentally friendly behaviors that employees strive to implement for the sake of achieving the environmental goals of the organization, such as turning off lights when leaving, printing on both sides, using stairs instead of elevators, and coming up with ideas to improve the environment (Lu et al, 2017; Ramus & Steger, 2000; Robertson & Barling, 2013; Russell & Griffiths, 2008). It has been demonstrated that the effectiveness of companies in implementing environmental strategies depends largely on employees' PEB (Chumg et al, 2019; Nisar et al, 2021; Onkila & Sarna, 2022; Saeed et al, 2019; Salvador & Burciaga, 2020; Unsworth et al, 2013). And there are many factors that influence employees' PEB, which can be broadly classified into individual‐level factors, leadership‐level factors, and organizational‐level factors (Al‐Ghazali & Afsar, 2021; Katz et al, 2022; Khalid et al, 2022; Luu, 2018; Sabbir & Taufique, 2022; Tariq et al, 2020; Uddin et al, 2021; Wood et al, 2021), where organization‐level factors have increasingly become a hot topic of research in recent years (Ansari et al, 2021; Cheema et al, 2020; Jaich, 2022).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Employees' PEB is a series of environmentally friendly behaviors that employees strive to implement for the sake of achieving the environmental goals of the organization, such as turning off lights when leaving, printing on both sides, using stairs instead of elevators, and coming up with ideas to improve the environment (Lu et al, 2017; Ramus & Steger, 2000; Robertson & Barling, 2013; Russell & Griffiths, 2008). It has been demonstrated that the effectiveness of companies in implementing environmental strategies depends largely on employees' PEB (Chumg et al, 2019; Nisar et al, 2021; Onkila & Sarna, 2022; Saeed et al, 2019; Salvador & Burciaga, 2020; Unsworth et al, 2013). And there are many factors that influence employees' PEB, which can be broadly classified into individual‐level factors, leadership‐level factors, and organizational‐level factors (Al‐Ghazali & Afsar, 2021; Katz et al, 2022; Khalid et al, 2022; Luu, 2018; Sabbir & Taufique, 2022; Tariq et al, 2020; Uddin et al, 2021; Wood et al, 2021), where organization‐level factors have increasingly become a hot topic of research in recent years (Ansari et al, 2021; Cheema et al, 2020; Jaich, 2022).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Prior researchers examined the predictors and outcomes of EEB for comprehending the creation of environmental-friendly and sustainable workplace. Several studies have associated individual-level factors to EEBs, such as subjective norms, pluralistic ignorance [27], employee-organisation fit [28], personal moral norms [1], moral reflectiveness and co-worker pro-environmental advocacy [29], environmental awareness, knowledge and concern [30]. In addition, certain studies focused on organisational-level influences, such as green human resource management practices [21], perceived corporate social responsibility [31], perceived organisational support [32], organisational climate [28], and incentives [33].…”
Section: Introductionmentioning
confidence: 99%
“…The supervisor-subordinate guanxi affects employees’ pluralistic ignorance, which, in turn, influences their pro-environmental behavior within organizations. 48 Employee low-carbon behavior is driven by a mixture of moral and personal norms and self-interest. 27 The moral kind of Taoism has a stronger effect on employee low-carbon behavior.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%